Seven families addition under class Polypetalae for flora of Todgarh-Raoli wildlife sanctuary, Rajasthan (Indian Journal of Arid Horticulture, 2020)
Todgarh-Raoli wildlife sanctuary is one of the protected areas expressing full range of habitat of Aravalli ecosystem. It is important from bio-geographical point of view the patches of Dhok and Salar forests. It has exceptional diversity and interspersion of habitat which includes areas of Dhok, Salar, dryland, seasonal streams, cascading mountains and newly formed sand dunes, formed on western hill aspects and fine grooves of mixed wood lands. This sanctuary makes an ecotone between hilly forests of Aravallis and Thar desert situated in the north-west. The hills of this sanctuary acts like a barrier, checking eastward extension of desert. Because this sanctuary have potential to rich plant wealth, which attracts botanist. Rajasthan is endowed with a wealth of a wide range of vegetation. It represents 1910 plant species belonging to 779 genera and 153 families. Out of these, 624 species belonging to 257 genera and 68 families under Polypetalae class in Rajasthan (Shetty & Singh, 1987). In the Aravalli range, Polypetalae represents 445 species belonging to 213 genera and 62 families (Otaghavari et al., 2015).
Keywords: dryland; Dhok; Salar